(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Contemporary economy forces enterprises to continuous building their competitiveadvantage. An organizational culture becomes a common platform of searching for thisadvantage. The future of an enterprise lays on its development . The organizationalculture is the base of a firms identity ,determines its success , being the source of itsdevelopment and the constituent of its proper image in the eyes of its customers.Because the organizational culture is differently understood by different scholars andpractitioners, hence diversity of definitions of this term. The aim of this paper is todepict the multiplicity of definitions and understanding of the organizational cultureand its creation for accomplishing organizational goals